2022
DOI: 10.37014/medpus.v29i3.2734
|View full text |Cite
|
Sign up to set email alerts
|

Peran Pustakawan Data Dalam Meningkatkan Literasi dan Kapasitas Pengelolaan Data Penelitian bagi Komunitas Penelitian dan Profesional Informasi di Indonesia

Abstract: Data librarians are responsible for managing research data, who play an active role in improving the literacy and capacity of the research community and information professionals. Some Indonesian programmes have emerged, but their role and readiness have not been studied. The aspects of personnel readiness to support research data management (RDM) are further discussed in this research, as obligated on the National System for Science and Technology Act No. 11 of 2019. This study was conducted to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Mengonsep dan memahami proses kurasi data penelitian Menurut Tammaro et al (2017) kurasi data merupakan wilayah tanggung jawab antara peneliti, pustakawan, dan profesional informasi di lingkungan perpustakaan (Nashihuddin 2019). Saat ini pengembangan bidang kurasi data digital berkembang secara cepat dan pada tahun 2007 peran kurasi data digital menjadi topik perdebatan terbaru baru dalam dunia penelitian, kebijakan, dan pendidikan (Kusumaningrum, Triasih, & Riyanto 2019;Nashihuddin 2019). Kemampuan pustakawan/pengelola perpustakaan Balitbangtan dalam mengkonsep dan proses kurasi data penelitian dan upaya penyelamatan data penelitian berdasarkan uji deskripsi didapat bahwa mereka (a) mampu menilai dan memilih data riset pertanian yang sudah diinput ke database; (b) memeriksa kelengkapan meta data riset pertanian di database; (c) mengecek dan meninjau konten file data penelitian pertanian dan mampu mengecek struktur data tabular di data penelitian pertanian.…”
Section: Kompetensi Pustakawan Balitbangtanunclassified
“…Mengonsep dan memahami proses kurasi data penelitian Menurut Tammaro et al (2017) kurasi data merupakan wilayah tanggung jawab antara peneliti, pustakawan, dan profesional informasi di lingkungan perpustakaan (Nashihuddin 2019). Saat ini pengembangan bidang kurasi data digital berkembang secara cepat dan pada tahun 2007 peran kurasi data digital menjadi topik perdebatan terbaru baru dalam dunia penelitian, kebijakan, dan pendidikan (Kusumaningrum, Triasih, & Riyanto 2019;Nashihuddin 2019). Kemampuan pustakawan/pengelola perpustakaan Balitbangtan dalam mengkonsep dan proses kurasi data penelitian dan upaya penyelamatan data penelitian berdasarkan uji deskripsi didapat bahwa mereka (a) mampu menilai dan memilih data riset pertanian yang sudah diinput ke database; (b) memeriksa kelengkapan meta data riset pertanian di database; (c) mengecek dan meninjau konten file data penelitian pertanian dan mampu mengecek struktur data tabular di data penelitian pertanian.…”
Section: Kompetensi Pustakawan Balitbangtanunclassified
“…Indonesia has a store of very rich humanities data that could benefit from further exploration (Wissik and Ďur co, 2015). One obstacle to such exploration is the lack of support for data curation activities, as can be seen from Yudhanto and Laksmi's (2021) examination of data curation activities at the Indonesian Institute of Sciences (LIPI) and Kusumaningrum's et al (2019) study of five institutions. Research has shown that data curation is strongly influenced by organizational structure, infrastructure, work culture and strategic considerations, which need to be supported by good relations between curators, data owners, institutions, technology staff and leadership (Miller, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia has a store of very rich humanities data that could benefit from further exploration (Wissik and Ďurčo, 2015). One obstacle to such exploration is the lack of support for data curation activities, as can be seen from Yudhanto and Laksmi’s (2021) examination of data curation activities at the Indonesian Institute of Sciences (LIPI) and Kusumaningrum’s et al . (2019) study of five institutions.…”
Section: Introductionmentioning
confidence: 99%